The Cambridge introduction to eighteenth-century poetry - Sitter, John E. (Cambridge ; New York : Cambridge University Press, 2011)
'For readers daunted by the formal structures and rhetorical sophistication of eighteenth-century English poetry, this introduction by John Sitter brings the techniques and the major poets of the period 1700-1785 triumphantly to life. Sitter begins by offering a guide to poetic forms ranging from heroic couplets to blank verse, then demonstrates how skilfully male and female poets of the period used them as vehicles for imaginative experience, feelings and ideas. He then provides detailed analyses of individual works by poets from Finch, Swift and Pope, to Gray, Cowper and Barbauld. An approachable introduction to English poetry and major poets of the eighteenth century, this book provides a grounding in poetic analysis useful to students and general readers of literature'--
Machine generated contents note: Introduction; Part I. Voice: 1. Voice in eighteenth-century poetry; 2. The Heroic couplet continuum; 3. Vocal engagement: reading Pope's An Essay on Criticism; 4. Talking in tetrameter; 5. Blank verse and stanzaic poetry; Part II. Poetic Consciousness: 6. Satiric poetry; 7. Pope as metapoet; 8. Metapoetry beyond Pope; Part III. Vision: 9. Reading visions; 10. Personification; 11. Prophecy and prospects of society; 12. Ecological prospects and natural knowledge; A concluding note: then and now; Suggested reading; Index.
Includes bibliographical references and index.
Keywords: English poetry -- 18th century -- History and criticism